Six transition patterns and seven capture types in different left bundle branch bipolar pacing configurations - Zhang, Lu; Jiang, Longfu; Luo, Binbin; Shen, Jiabo; Wu, Hao; Zeng, Weifang (Frontiers in Cardiovascular Medicine, 2024)
Aims This study aims to explore the different transition patterns and capture types during two bipolar pacing tests based on the selective left bundle branch (LBB) capture determined by the continuous pacing and recording technique. Methods In total, 67 patients completed two unipolar and two bipolar pacing tests based on selective LBB capture during screwing-in for left bundle branch pacing (LBBP) using the continuous pacing and recording technique. The electrophysiological characteristics and potential mechanisms of different pacing configurations were further evaluated in this study. Results We found six transition patterns and derived seven capture types in two bipolar pacing tests according to the analysis of continuous electrocardiogram and electrogram changes. Compared with the conventional configuration of “Tip−Ring+” bipolar pacing, “Ring−Tip+” testing had a lower threshold for simultaneous capture of the LBB and the left and right ventricular septum myocardium (1.57 vs. 2.84 V at 0.5 ms) and was the only configuration to yield the peculiar “LBBP + right ventricular septum pacing (RVSP)” capture type. Conclusions In this study, we observed for the first time that “Ring−Tip+” bipolar pacing allows for a lower clinically applicable pacing threshold for simultaneous capture of the LBB and left and right ventricular septum myocardium, and the peculiar “LBBP + RVSP” capture type. This may be a more advantageous physiological pacing configuration, warranting further investigation and application in the future. Lay summary Based on the specific selective LBB capture, we first found six transition patterns and derived seven capture types in two bipolar pacing tests due to the different thresholds of the LBB, left ventricular septal myocardial, and right ventricular septal myocardial. Compared with the conventional configuration of “Tip−Ring+” bipolar pacing, “Ring−Tip+” testing had a lower threshold for simultaneous capture of the LBB and the left and right ventricular septum myocardium (1.57 vs. 2.84 V at 0.5 ms) and was the only configuration to yield the peculiar “LBBP + RVSP” capture type. More pacing strategies should be released and investigated to achieve the best physiological pacing according to the individualized electrophysiological characteristics of patients.